2007
DOI: 10.1590/s0102-09352007000100024
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal potencial of Sapindus saponaria (Sapindaceae) against Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae)

Abstract: The larvicidal potential of the crude ethanolic extracts (CEE) of the stem peel of Sapindus saponaria was evaluated against Rhipicephalus sanguineus. Lethal concentrations (LC), were calculated by preparing CEE solutions at different concentrations in distilled water. Larvae fasted for 14-21 days were utilized in the bioassays, after incubation of engorged females collected from infested environments frequented by dogs in several neighborhoods of Goiânia, GO. Bioassays were performed in a specially constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 13 publications
(12 reference statements)
0
3
0
2
Order By: Relevance
“…53 As another alternative to conventional chemical control of ticks, promising results have been obtained with the use of organonatural substances -"green acaricides" -in the control of vectors of medical and veterinary importance, including R. sanguineus. 30,35,36,[54][55][56][57] Botanical substances with acaricidal properties meet the need for less polluting and biodegradable compounds, which leads to a reduction in the aggression to the environment exerted by conventional chemical acaricides and provide an environmental awareness of the need to preserve natural resources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 As another alternative to conventional chemical control of ticks, promising results have been obtained with the use of organonatural substances -"green acaricides" -in the control of vectors of medical and veterinary importance, including R. sanguineus. 30,35,36,[54][55][56][57] Botanical substances with acaricidal properties meet the need for less polluting and biodegradable compounds, which leads to a reduction in the aggression to the environment exerted by conventional chemical acaricides and provide an environmental awareness of the need to preserve natural resources.…”
Section: Resultsmentioning
confidence: 99%
“…The impregnated papers methodology, also known as larval packet test (lpt), was used. This method was adapted by Fernandes and Freitas 30 from previously described methods, mainly those of FAO, 32,33 Fernandes 6,34 and Fernandes et al 35,36 Adaptations of the FAO method were carried out with the aim of increasing practicality and reducing costs, but without loss of efficiency, having been tested and improved, with satisfactory results in the evaluation of the acaricidal activity of chemical and botanical substances on different species of Ixodidae, e.g., R. sanguineus, R. microplus and Amblyomma cajennense. Further details of the methodology can be found in Fernandes and Freitas.…”
Section: Bioassays For Evaluating Larval Sensitivitymentioning
confidence: 99%
“…Em outro trabalho, após o período de aplicação de 24h, observou-se a redução do número médio de ovos de 138,0 (testemunha) para 85,0 (JESUS et al, 2011). Santos et al (2008) (FERNANDES et al, 2007).…”
Section: Resultsunclassified
“…Périco et al (2015) reported that plants of the Sapindaceae family have saponins and tannins. The high saponin content of Sapindaceae fruits has foam-forming properties and can be used as an insecticide (Fernandes et al, 2007), which may cause an inhibitory effect on P. xylostella oviposition. Saponins are substances mainly related to the defense system.…”
Section: Discussionmentioning
confidence: 99%